An Analysis of Assertive Illocutionary Acts on Social Media - Maria Olivia Christina Sianipar (Universitas Potensi Utama, 2022)
This study aims to determine the use of assertive illocutionary act. The focus of this research is writing in the form of status that contains different topics in several social media today such as Instagram and Twitter. The datas are taken randomly from different accounts in Instagram and Twitter. This research is a qualitative descriptive study in which the data in this study were collected through documentation and note-taking techniques. The results of data analysis reveal that the use of assertive illocutionary act is widely available and used in social media such as Instagram and Twitter. There are three kinds of assertive illocutionary act that are found in this research they are reporting, stating/ telling, and suggesting. The use of assertive illocutionary act that appear the most is reporting. The second one that has many assertive illocutionary acts is stating/telling. The fewest assertive illocutionary acts are suggesting. In the usage of assertive illocutionary act, the meaning of the implicature appeared, among others, expressed opinions, express thoughts, express wishes, etc. There is always interesting to read Instagram and Twitter from different accounts and get different good things or aspects on different kinds of assertive illocutionary acts.